Antioxidants in Italian Head Lettuce (Lactuca sativa var. capitata L.) Grown in Organic and Conventional Systems under Greenhouse Conditions. Issue 1 (8th April 2013) - Durazzo, Alessandra; Azzini, Elena; Lazzé, Maria Claudia; Raguzzini, Anna; Pizzala, Roberto; Maiani, Gianluca; Palomba, Lara; Maiani, Giuseppe
Abstract Lettuce belongs to the Asteraceae family and it is native of the Mediterranean region. In our research, the effect of cultivation practices (organic versus conventional) on antioxidants in Italian head lettuce (Lactuca sativa var. capitata L.) grown in greenhouse was investigated. Bioactive molecule levels, antioxidant properties and the cytotoxicity of polyphenolic extracts from the edible part of head lettuce in Caco‐2 cells were determined. FRAP values are 5.33 ± 0.35 and 6.35 ± 0.08 mmol/kg in organic products and 4.83 ± 0.16 and 1.80 ± 0.04 mmol/kg in conventional products. FRAP values differ significantly (P < 0.001) between organic and conventional lettuces harvested in September. Significant differences are found between organic and conventional extracts in some target compounds such as quercetin, rutin, lutein, β‐carotene and vitamin C. No difference in biological effect is observed between organic and conventional products harvested in July and in September, whereas a major cytotoxicity is found for polyphenol extracts derived from organic and conventional lettuces harvested in September. Practical Applications Nowadays, a new image of agriculture is emerging: agricultural production systems are closely related to the needs of consumers and to the search of products that meet food quality and safety. The results of this investigation highlighted the importance of factors such as cultivar, agronomic practices, climatic conditions, degree of ripeness, time of harvest and storage conditions. The variation of these elements represents, in fact, a key tool to obtain healthful and more nutritious food crops by increasing and maximizing the levels of bioactive molecules in foods. Our results suggest a potential to increase the commercial production of the selected specialty leafy greens.